Efeito da dieta suplementada com vitamina E e cobre nas respostas metabólicas e antioxidantes de matrinxã, Brycon cephalus (Gunther, 1869), frente à hipóxia - Santos, Laila Romagueira Bichara dos (Universidade Federal de São Carlos, 2006)
The diet is an essential factor for the growth and maintenance of vital functions as well as to ability fish to reply the stressors. The reduction of oxygen concentration in the water may occur mainly in fish culture ponds, and may reduce the growth rate of the animals due to metabolism changes. Therefore the supplementation of the diet with copper and vitamin E can improve the animals defenses. Matrinxã specimens, Brycon cephalus, promising specie for fisheries, were fed with commercial ration (Co) and rations supplemented with vitamin E (E) and vitamin E+copper (E+Cu) during 30 days following by exposure to hypoxia (Hpx) during 24h (DO = 2,87 mgO2/L). The hematological variables [hematocrit (Hct), hemoglobin concentration ([Hb]), red blood cells (RBC), mean corpuscular volume (MCV), mean hemoglobin concentration (MHC) and mean corpuscular hemoglobin concentratrion (MCHC)]; metabolic changes such as concentrations of glucose, lactate, piruvate, ammonia, glycogen and protein in liver, red and white muscles and plasma (exception of glycogen) and, the oxidative stress parameters as concentration of peroxide lipids (HP), activity of superoxide dismutase (SOD), glutathione peroxidase (GHS-Px) and catalase (CAT) (exception in plasma) in the same tissues, including the gills and heart. The diets E and E+Cu may increase the aerobic capability of matrinxã when in hypoxic condition as there were increases of [Hb] and MCHC in group E+Cu and an increase in MCHC in E accompanied by an increase in the pyruvate and no change in lactate in most of tissues of fish fed wit supplemented diets. These results support the view that the both supplemented diets, and mainly the E+Cu, seem to increased the aerobic capacity of matrinxã during hypoxia. Hypoxia increased HP concentration only in the plasma and the supplemented diet change the oxidative stress, hematological and metabolical parameters. The diet E reduced HP concentration in the heart and red muscles during hypoxia and the diet E+Cu increased the enzyme concentration and activity without generated HP increase, even in conditions of higher aerobic metabolism. The obtained results suggest that the supplemented diets increased the aerobic capacity of matrinxã during hypoxia without increasing oxidative stress, while the metabolic adjustments front to the reduced concentration of O2 had been efficient to maintain the O2 delivery to the tissues since the hypoxia only modified the parameters analyzed when in association with the differentiated diets.
Keywords: Peixe - fisiologia; Antioxidante; Metabolismo; Hipóxia; CIENCIAS BIOLOGICAS::FISIOLOGIA